2022
DOI: 10.3389/fpsyg.2022.975374
|View full text |Cite
|
Sign up to set email alerts
|

Flashforward imagery in speech anxiety: Characteristics and associations with anxiety and avoidance

Abstract: Speech anxiety (SA) is a highly prevalent social fear. Prospective ‘flashforward’ (FF) imagery of an upcoming social catastrophe may be a particularly important cognitive factor in SA persistence via eliciting anxiety and avoidance behaviors. Since earlier research on imagery and social anxiety has not strictly differentiated between types of negative imagery, the occurrence, precise features, and impact of FF imagery remain unclear. We therefore examined the phenomenological characteristics of FF imagery in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This is of interest as previous findings have shown that these forms of negative imagery appear prevalent and relevant as well in social anxiety (e.g., Ashbaugh, Fishman, and Houle‐Johnson 2019; Homer and Deeprose 2018; Thunnissen et al. 2022). Questions remain on how to best determine the target image(s) that would also be of key relevance for treating social anxiety.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This is of interest as previous findings have shown that these forms of negative imagery appear prevalent and relevant as well in social anxiety (e.g., Ashbaugh, Fishman, and Houle‐Johnson 2019; Homer and Deeprose 2018; Thunnissen et al. 2022). Questions remain on how to best determine the target image(s) that would also be of key relevance for treating social anxiety.…”
Section: Discussionmentioning
confidence: 89%
“…Besides, imagery vividness has previously shown inconsistencies in terms of its relationship with social anxiety symptoms (e.g., Thunnissen et al. 2022). Future research could therefore include other imagery characteristics and imagery appraisals that may relate to the detrimental impact of negative images in assessing intervention effects (e.g., imagery appraisals such as linked beliefs, as was assessed several times by studies on IR [see Table S2.1 in Appendix S2], or subjective probability of imagined outcomes; e.g., Landkroon et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst these structures are involved in the production of mental imagery, it is important to note that the amygdala also seems to be involved when negative mental imagery is generated—imagery that envisages negative outcomes in performance ( MacNamara, 2018 ). Negative imagery has been recognised in sports literature as being detrimental to performance (see Morris et al, 2005 ), and is associated with anxiety and negative performance outcomes in psychology research ( Thunnissen et al, 2022 ). Indeed, anxiety initiates a stress response: muscle tension, activation of the sympathetic nervous system, and the initiation of “fight or flight” reactions, which can impede both retrieval of stored information and knowledge acquisition (see Perry, 2006 ).…”
Section: Introductionmentioning
confidence: 99%